Emollients for eczema - Oranje, Arnold P (Cochrane Database Syst Rev, 2016)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of topical application of emollients in eczema. Specifically, we wish to examine: 1. whether application of emollients is enough to control mild eczema; 2. whether application of emollients when used concurrently with active treatments such as topical corticosteroid creams can reduce consumption of topical corticosteroid creams without compromising disease severity; 3. whether the use of emollients inbetween periods of deterioration of eczema helps to prevent future deterioration of eczema; and 4. how different methods of application of emollients influence their efficacy. We will examine: direct application during the day; or after a bath or in spray form; or as a bath emollient. direct application during the day; or after a bath or in spray form; or as a bath emollient.